Research on the impact of crowd queuing behavior on construction personnel evacuation - Zeng Meiting; Zhao Daoliang; Yang Li; Lu Yun; Shi Lei; Hu Zhao (E3S Web of Conferences, 2021)
The evacuation channel is an important way to connect the room and the security exit. This paper studies the impact of queuing behavior on the evacuation of people in the building channel. In this paper, Considering the factors of evacuation channel width, personnel density and speed, queuing form, different queuing queues, etc., using Massmotion software simulation. The research shows that for different queuing methods, the evacuation efficiency of queuing by shares is less affected by the width of the channel, there is a critical channel width for the evenly divided queues, and the evacuation efficiency of the different queuing queues is inconsistent; under different widths, the personnel density and speed have different evacuation efficiency Law of influence. The research in this paper can provide a certain reference for the design of building evacuation.